Exploring consumers' usage intention of reusable express packaging: an extended norm activation model - Song, Jiawen (2023)
The express delivery industry is experiencing rapid growth, which has led to an environmental problem with express packaging. To this end, utilising reusable express may be a viable solution. This study aims to understand consumers' usage of reusable express packaging. A norm-based perspective is proposed by integrating subjective norm and environmental concern into an extended norm activation model. For the data analysis, a structural equation model is employed to analyse 400 valid responses collected from an online questionnaire survey. The empirical results show that: (1) consumers’ behavioural intention is strongly influenced by personal norm, and the personal norm is determined by their awareness of consequences and ascription of responsibility; (2) the behavioural intention is also enhanced by subjective norm, which is further shaped by the media influence and perceived policy effectiveness; and (3) environmental concern influences consumers' behavioural intention both directly and indirectly through personal norm. The research findings contribute to the theoretical study of reusable express packaging and provide practical implications for the promotion of reusable express packaging.